Lipopolysaccharide-induced epididymitis modifies the transcriptional profile of Wfdc genes in mice - Andrade, Alexandre D. [UNESP]; Almeida, Priscila G. C. [UNESP]; Mariani, Noemia A. P. [UNESP]; Freitas, Geanne A.; Kushima, Helio [UNESP]; Filadelpho, Andre L. [UNESP]; Spadella, Maria Angelica; Avellar, Maria Christina W.; Silva, Erick J. R. [UNESP] (Oxford Univ Press Inc, 2021)
Whey-acidic protein four-disulfide core domain (WFDC) genes display putative roles in innate immunity and fertility. In mice, a locus on chromosome 2 contains 5 and 11 Wfdc genes in its centromeric and telomeric subloci, respectively. Although Wfdc genes are highly expressed in the epididymis, their contributions to epididymal function remain elusive. Here, we investigated whether Wfdc genes are regulated in response to lipopolysaccharide (LPS)-induced epididymitis, an inflammatory condition that impairs male fertility. We induced epididymitis in mice via (i) interstitial LPS injection into epididymal initial segment and (ii) intravasal LPS injection into the vas deferens towards cauda epididymis. Interstitial and intravasal LPS induced a differential upregulation of inflammatory mediators (interleukin 1 beta, interleukin 6, tumor necrosis factor, interferon gamma, and interleukin 10) in the initial segment and cauda epididymis within 72 h post-treatment. These changes were accompanied by a time-dependent endotoxin clearance from the epididymis. In the initial segment, interstitial LPS upregulated all centromeric (Slpi, Wfdc5, Wfdc12, Wfdc15a, and Wfdc15b) and five telomeric (Wfdc2, Wfdc3, Wfdc6b, Wfdc10, and Wfdc13) Wfdc transcripts at 24 and 72 h. In the cauda epididymis, intravasal LPS upregulated Wfdc5 and Wfdc2 transcripts at 24 h, followed by a downregulation of Wfdc15b and three telomeric (Wfdc6a, Wfdc11, and Wfdc16) gene transcripts at 72 h. Pharmacological inhibition of nuclear factor kappa B activation prevented LPS-induced upregulation of centromeric and telomeric Wfdc genes depending on the epididymal region. We show that LPS-induced inflammation differentially regulated the Wfdc locus in the proximal and distal epididymis, indicating region-specific roles for the Wfdc family in innate immune responses during epididymitis. Summary Sentence LPS-induced inflammation in the mouse epididymis differentially regulated the transcript levels of centromeric and telomeric Wfdc genes in the Wfdc locus on chromosome 2; an effect partially prevented by blocking LPS-TLR4-NFKB pathway. [GRAPHICS]
Keywords: epididymis; epididymitis; Whey-acidic protein four-disulfide core (WFDC)-type proteins; toll-like receptor 4; lipopolysaccharide